2011
DOI: 10.1111/j.1365-2230.2011.04152.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status in patients with lichen planus

Abstract: Lower serum levels of vitamin C in patients with LP indicates that free radicals and the resulting oxidative damage may be important in the pathogenesis of LP lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…The fact that antioxidant vitamins are effective against oxidative stress may explain the significant difference between healthy individuals and patients with OLP. Consistent with our findings, Barikbin et al,21 found a significant decrease in salivary levels of vitamin C and vitamin E in patients with OLP. In contrast to our study, Nagao in a case control study about serum antioxidant in patients with OLP showed higher levels of retinol in OLP 7…”
Section: Discussionsupporting
confidence: 93%
“…The fact that antioxidant vitamins are effective against oxidative stress may explain the significant difference between healthy individuals and patients with OLP. Consistent with our findings, Barikbin et al,21 found a significant decrease in salivary levels of vitamin C and vitamin E in patients with OLP. In contrast to our study, Nagao in a case control study about serum antioxidant in patients with OLP showed higher levels of retinol in OLP 7…”
Section: Discussionsupporting
confidence: 93%
“…Lichen planus is a chronic, inflammatory disease affecting the skin and oral mucosa [26]. Cutaneous LP was observed in 15% of an OLP population and more than 50% of patients with 2.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of published data indicated convincingly that patients with MS had lower serum uric acid than healthy controls, and advocated serum uric acid low level as a potential biomarker for multiple sclerosis [49]. Low plasma uric acid levels were also associated with neurological disorders [49], [50], [51], Parkinson [52], [53], [54], [55], [56], and Alzheimer [57], [58] disease, Pemphigus vulgaris, an autoimmune disorder characterized by blistering and sores (erosions) of the skin and mucous membranes [59], and lichen planus, an autoimmune inflammatory disease of the mucocutaneous tissue [60], [61], which was also associated with low uric acid levels in saliva [62].…”
Section: Defense Against Neurological and Autoimmune Diseasesmentioning
confidence: 99%